Implementasi Metode Bisection dalam Menentukan Nilai Ambang Target Penurunan Tingkat Kemiskinan di Provinsi Jawa Tengah Tahun 2025 - Istnaniah Hani Salami; Dimas Maulidani; Ari Wibowo (FKIP Universitas Mataram, 2026)
Poverty remains a central issue in Indonesia’s development planning, particularly in Central Java Province, where poverty rates consistently exceed the national average. The Human Development Index (HDI) serves as a composite indicator reflecting quality of life through education, health, and living standards. This study aims to determine the minimum HDI thresholds required for regencies/cities in Central Java to achieve targeted poverty rates (8%, 9%, 10%, and 11%) by integrating simple linear regression with the bisection method. The data consist of HDI values for 2024 and poverty rates for 2025 across 35 regencies/cities, obtained from the Central Statistics Agency (BPS). The regression model produced the equation K(x) = 47.6038 − 0.5170x with a coefficient of determination (R²) of 0.64, indicating that HDI explains 64% of poverty variation. The bisection method converged in 23 iterations with a final error of 0.000004. The resulting HDI thresholds range from 70.80 to 76.60 depending on the target. These findings provide a quantitative basis for policymakers to design more effective and evidence-based poverty reduction strategies.